2007
DOI: 10.1136/emj.2006.044388
|View full text |Cite
|
Sign up to set email alerts
|

Is CT effective in cases of upper oesophageal fish bone ingestion?

Abstract: Diedl JL, Mercat A, et al. Helium/oxygen mixture reduces the work of breathing at the end of the weaning process in patients with severe chronic obstructive pulmonary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…In a review of 4 small prospective, nonrandomized studies comparing plain radiographs to CT, CT had a sensitivity of 100% in all 4 studies and there was just 1 false positive in all 80 patients pooled from the studies. 8 In a recent study by Park et al, 9 64-slice multidetector computed tomography (MDCT) demonstrated 100% sensitivity among 66 patients, versus 51.7% among plain radiographs. With this apparent superiority in mind, the clinician must balance the associated time, cost, and radiation of CT against the poor performance of clinical evaluation and plain radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…In a review of 4 small prospective, nonrandomized studies comparing plain radiographs to CT, CT had a sensitivity of 100% in all 4 studies and there was just 1 false positive in all 80 patients pooled from the studies. 8 In a recent study by Park et al, 9 64-slice multidetector computed tomography (MDCT) demonstrated 100% sensitivity among 66 patients, versus 51.7% among plain radiographs. With this apparent superiority in mind, the clinician must balance the associated time, cost, and radiation of CT against the poor performance of clinical evaluation and plain radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review in 2007 looking at over 150 patients across four studies found that CT is more effective than plain radiography at identifying and excluding impacted oesophageal fish and chicken bones 7. However, they also noted that plain radiography is sensitive enough for positive results to warrant oesophagoscopy without further imaging, and should thus continue being utilised as the first line radiological investigation.…”
Section: Discussionmentioning
confidence: 99%
“…魚骨異物は15歳以下の小児の異物誤飲の中で最も多い 2)とされているが,本研究ではとくに2歳から6歳の幼児の割合が最も多かった。また,ほとんどの症例で魚骨は口蓋扁桃を含んだ中咽頭に確認された。最近の耳鼻咽喉科領域の報告でも,小児ではほとんどの症例において中咽頭に魚骨が確認されていた 2)。これらは,魚骨異物の好発年齢と口蓋扁桃が生理的に腫大している時期が一致していることが一つの要因として考えられている 3)。また,主に成人を対象とした既存の報告では,魚骨異物の症状のうち“鋭い刺すような痛み”が最も陽性的中率が高いと報告されている 4)が,小児では正確な症状を訴えることは難しい。来院時に唾液を嚥下できない場合や魚を摂取後から機嫌が悪い,ずっと泣いている,また飲食が取れない,あるいは痛みの訴えが強い場合などは,口腔内の観察で魚骨が確認できなくとも,追加検査を考慮したほうがよいと考えられる。本研究で,実際に追加検査を行った症例は約20%であり,2歳以下では主にX線が,それ以上の年齢では鼻咽喉ファイバーやCTが選択されていた。文献的には,魚骨異物に対するX線は感度32%,特異度91% 4),鼻咽喉ファイバーは感度65%,特異度100%であり 5),両者とも魚骨の確認ができなくても否定することはできないと言える。CTは被曝の問題があるが,感度,特異度ともに100%との報告 6)など,その有効性 6), 7), 9)が指摘されている。そのため,被曝を考慮すると鼻咽喉ファイバーを優先させ,ファイバーで所見はないが上記症状が残存する症例,または鼻咽喉ファイバーが不可能な症例には,CTを追加するという方針が妥当であろう。…”
Section: 考  察unclassified